Photoluminescent properties of the promising red-emitting phosphor LiGd1−xEux(MoO4)2 for WLEDs. (July 2015) - Li, Juan; Lu, Cheng; Lu, He; Yang, Xiumei; Zhu, Bo; Yu, Hongyou; Sheng, Jiawei; Che, Shenglei
Abstract: A series of LiGd1− x Eu x (MoO4 )2 ( x =0.01–1) red-emitting phosphors were synthesized by the conventional solid-state reaction method. XRD was used to determine the structure of the samples, showing that the products are single phased with sheelite-like structure. The photoluminescent properties were characterized by a fluorescence spectrophotometer and the effects of the calcination temperature, the holding time as well as the doping concentration, especially the low doping concentration of Eu 3+, were discussed. Upon excitation with 395 nm, the LiGd(MoO4 )2 :Eu 3+ phosphors show strong red emission lines at 617 nm which are ascribed to the forced electric dipole transition 5 D0 – 7 F2 of Eu 3+ . The appropriate calcination temperature and holding time are 900 °C and 5 h, respectively. With increasing Eu 3+ doping concentration, the emission intensity of the samples is enhanced and no obvious concentration quenching occurs. The prepared samples are potential red phosphors for near UV White LEDs application.